Unravelling the transport of moisture into the Saharan Air Layer using passive tracers and isotopes - Dahinden, Fabienne; Aemisegger, Franziska; Wernli, Heini; Pfahl, Stephan (2023)
The subtropical free troposphere plays a critical role in the radiative balance of the Earth. However, the complex interactions controlling moisture in this sensitive region and, in particular, the relative importance of long-range transport compared to lower-tropospheric mixing, remain unclear. This study uses the regional COSMO model equipped with stable water isotopes and passive water tracers to quantify the contributions of different evaporative sources to the moisture and its stable isotope signals in the eastern subtropical North Atlantic free troposphere. In summer, this region is characterized by two alternating large-scale circulation regimes: (i) dry, isotopically depleted air from the upper-level extratropics, and (ii) humid, enriched air advected from Northern Africa within the Saharan Air Layer (SAL) consisting of a mixture of moisture of diverse origin (tropical and extratropical North Atlantic, Africa, Europe, the Mediterranean). This diversity of moisture sources in regime (ii) arises from the convergent inflow at low levels of air from different neighbouring regions into the Saharan heat low (SHL), where it is mixed and injected by convective plumes into the large-scale flow aloft, and thereafter expelled to the North Atlantic within the SAL. Remarkably, this regime is associated with a large contribution of moisture that evaporated from the North Atlantic, which makes a detour through the SHL and eventually reaches the 850–550 hPa layer above the Canaries. Moisture transport from Europe via the SHL to the same layer leads to the strongest enrichment in heavy isotopes (δ2H correlates most strongly with this tracer). The vertical profiles over the North Atlantic show increased humidity and δ2H and reduced static stability in the 850–550 hPa layer, and smaller cloud fraction in the boundary layer in regime (ii) compared to regime (i), highlighting the key role of moisture transport through the SHL in modulating the radiative balance in this region.